An interpretative phenomenological analysis of stress and coping in first year undergraduates. (15th October 2012) - Denovan, Andrew; Macaskill, Ann
<x xml:space="preserve">Abstract</x> In the UK, changes to the higher education system have increased the range of stressors experienced by students above those traditionally associated with the transition to university. Despite this, there is little qualitative research examining how students experience and cope with the adjustment to university. The experience of the transition was investigated in depth amongst 10 first year UK undergraduates. Purposive sampling resulted in a group with demographics similar to national statistics on UK undergraduates. Semi‐structured interviews were used beginning with a content specific vignette to develop rapport. Interpretative phenomenological analysis was utilised to analyse the transcripts and quality checks were implemented to increase the validity of the analysis. Five main themes were identified: all the change, with subthemes of independent living, homesickness, differences between post‐compulsory education and university; expectations of university; academic focus with subthemes of self‐discipline, motivation, learning from experience; support network with subthemes of establishing a support network, support for coping with problems; and difficulties with subthemes of difficulties experienced with housemates, finances and employment, and academic difficulties. Students used a range of coping strategies.By identifying the role of positive psychological strengths such as optimism, hope, self‐efficacy and self‐control in coping with stress and facilitating positive adaptation, the study locates positive psychological strengths within a transactional understanding of stress and provides depth and relevance to their role in facilitating adjustment. Such qualitative research is rare in the positive psychology and stress literature. Suggestions for easing the transition are made.